2008
DOI: 10.1097/mao.0b013e318170b60b
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Factors in Pediatric Cochlear Implantation and Their Early Effects on Electrode Activation and Functional Outcomes

Abstract: Objective-To assess the impact of surgical factors on electrode status and early communication outcomes in young children in the first 2 years of cochlear implantation.Study Design-Prospective multicenter cohort study. Setting-Six tertiary referral centers.Patients-Children 5 years or younger before implantation with normal nonverbal intelligence. Intervention-Cochlear implant operations in 209 ears of 188 children.Main Outcome Measures-Percent active channels, auditory behavior as measured by the Infant Toddl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 14 publications
3
29
1
1
Order By: Relevance
“…The incidence of complications is reported at 4.5-34.7% with major complications 2.3-13.9% [10][11][12][13][14][15]. The minor wound complication rate without major complications in our series compares favorably with other reported studies.…”
Section: Discussionsupporting
confidence: 84%
“…The incidence of complications is reported at 4.5-34.7% with major complications 2.3-13.9% [10][11][12][13][14][15]. The minor wound complication rate without major complications in our series compares favorably with other reported studies.…”
Section: Discussionsupporting
confidence: 84%
“…Francis et al (21) recently reported on the impact of functioning electrode status on early communication outcomes in children in the prospective Childhood Development after Cochlear Implantation study. Incomplete electrode array implantation was reported in 4% of patients, with an additional 28 of 209 devices requiring electrode deactivation after initial programming.…”
Section: Discussionmentioning
confidence: 97%
“…Meningitis included children with an etiology of meningitis reported in their medical history or imaging findings. “Abnormal” included findings of cystic cochlea, hypotrophic cochlea, cochlear dysplasia, dilation of the cochlea and vestibule and all other findings indicating abnormal inner ear anatomy [35]. …”
Section: Methodsmentioning
confidence: 99%